2017
DOI: 10.1002/adsc.201600373
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Heterobimetallic Lanthanide Alkoxide Catalyst for Transamidation of Amides under Solvent‐Free Conditions

Abstract: A practical heterobimetallic lanthanide‐catalyzed transamidation of primary, secondary and tertiary amides with aliphatic and aromatic amines has been developed. The methodology was also applied to the weakly reactive thioamides to demonstrate its versatility and wide substrate scope. The heterobimetallic lanthanide catalysts showed high catalytic activity and a wide scope of substrates with good to excellent yields under solvent‐free conditions. Efficient activation of the transamidation can be realized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 125 publications
0
8
0
Order By: Relevance
“…Taking advantage of the insertion of such catalysts into the C-N bond, the groups of Garg 143,144 and Hu 145 in the case of nickel-catalysis, and Szostak in the case of palladium catalysis, 146 have introduced a variety of transamidation protocols with primary and secondary amines (Scheme 39a). Other metals have also been employed in isolated cases: in this regard, lanthanide catalysts have been shown to activate primary amides for transamidation reactions with a range of amines (Scheme 39b, top), 147 and-mimicking biological systems-especially tailored nicotinate amides can be alcoholised using zinc catalysis (Scheme 39b, bottom). 148 Remarkably, in 2017, Szostak and co-workers reported a transamidation reaction that proceeds even in the absence of a transition metal catalyst, exploiting the increased electrophilicity of non-planar amides.…”
Section: Smi 2 -Mediated Functionalisationmentioning
confidence: 99%
“…Taking advantage of the insertion of such catalysts into the C-N bond, the groups of Garg 143,144 and Hu 145 in the case of nickel-catalysis, and Szostak in the case of palladium catalysis, 146 have introduced a variety of transamidation protocols with primary and secondary amines (Scheme 39a). Other metals have also been employed in isolated cases: in this regard, lanthanide catalysts have been shown to activate primary amides for transamidation reactions with a range of amines (Scheme 39b, top), 147 and-mimicking biological systems-especially tailored nicotinate amides can be alcoholised using zinc catalysis (Scheme 39b, bottom). 148 Remarkably, in 2017, Szostak and co-workers reported a transamidation reaction that proceeds even in the absence of a transition metal catalyst, exploiting the increased electrophilicity of non-planar amides.…”
Section: Smi 2 -Mediated Functionalisationmentioning
confidence: 99%
“…In 2017, Sheng and co-workers reported transamidation of amides catalyzed by heterobimetallic lanthanide alkoxide catalysts (Scheme 53). 82 They found that neodymiumbased catalyst, Nd 2 Na 8 (OCH 2 CF 3 ) 14 (THF) 6 , showed the highest activity. This method works well with 1° amides, DMF, and DMAc, as well as various aliphatic and aromatic amines to give the desired amide products in good to excellent yields.…”
Section: Scheme 48 T-buok-promoted Transition-metal-free Transamidatimentioning
confidence: 99%
“…Nevertheless, other less important catalysts have to be superficially mentioned, including manganese oxide (MnO 2 ), which was used under solvent-free conditions [ 34 ] with a limited substrate scope but with good yields. The use of lanthanides has also been described; in particular, a bimetallic lanthanum alkoxide [ 35 ], and immobilized Ce(III) [ 36 ] were used as heterogeneous catalysts with the associated advantages, such as easy catalyst recovery and low catalyst charge, but also with the normal issues, such as the catalyst preparation and activation. Some more innovative catalysts have been prepared and used successfully in transamidation.…”
Section: Metal-catalyzed Direct Transamidationsmentioning
confidence: 99%